The Long-term Role of Non-traditional Banking in Profitability and risk profiles: Evidence from a panel of U.S. banking institutions - Apergis, Nicholas (Pergamon, 2014)
The goal of this empirical study is to identify empirically and on a panel basis how non-traditional bank activities affect directly the profitability and risk profiles of the financial institutions involved in such activities. Through a dataset that covers 1,725 U.S. financial institutions involved in non-traditional bank activities spanning the period 2000-2013 and the methodology of panel cointegration, the empirical findings document that non-traditional bank activities exert a positive effect on both the profitability and the insolvency risk. The results could be important for regulators given they could serve as a pre-warning signal that sends a clear message to regulators about the potential systemic risk that exists within the financial markets.